Muscle fiber type, Achilles tendon length, potentiation, and running economy - Hunter, G. R.; McCarthy, J. P.; Carter, S. J.; Bamman, M. M.; Gaddy, E. S.; Fisher, G.; Katsoulis, K.; Plaisance, E. P.; Newcomer, B. R. (The Journal of Strength and Conditioning Research, 2015)
The purpose of this investigation was to develop a potential model for how muscle fiber type, Achilles tendon length, stretch-shortening cycle potentiation (SSCP), and leg strength interact with running economy. Twenty trained male distance runners 24-40 years of age served as subjects. Running economy (net oxygen uptake) was measured while running on a treadmill. Leg press SSCPforce and SSCPvelocity were determined by measuring the difference in velocity between a static leg press throw and a countermovement leg press throw. Vertical jump SSCP was determined by measuring the difference in jump height between a static jump and a drop jump from a 20.3-cm bench. Tendon length was measured by magnetic resonance imaging, and muscle fiber type was made from a vastus lateralis muscle biopsy. Type IIx muscle fiber percent (r = 0.70, p < 0.001) and leg strength (r = 0.95, p < 0.001) were positively and independently related to late eccentric force development. Achilles tendon length (r = 0.42, p = 0.05) and late eccentric force during stretch-shortening cycle (r = 0.76, p < 0.001) were independently related to SSCPforce. SSCPforce was related to SSCPvelocity, which in turn was related to running economy (r = 0.61, p < 0.01). These results suggest that longer Achilles tendon length, type II fiber, and muscular leg strength may enhance the potential for SSCP, running economy, and physiological effort while running.